PENERAPAN METODE PEMBIASAAN KARAKTER RELIGIUS BERBASIS BUDAYA SEKOLAH DI SMA MUHAMMADIYAH 2 SINGARAJA - Supini (Jurnal Media Komunikasi Pendidikan Pancasila dan Kewarganegaraan, 2022)
The study discussed the application of the school's method of cultured religious makeup. The study was focused on the school's cultural refraction of religious characters. The study aims to know: (1) how to implement the application of the school's culture-based religious character-based method of breeding in the school's values and beliefs at the 2 singaraja muhammadiyah high school (2) what programs are applied to the student's religious breeding method at muhammadiyah 2 singaraja high school. (3) the study USES a qualitative descriptive approach to describe systematically, factual, and accurately the facts, situations or events and characteristics of the population. The technique for introducing informants in this study is observation, document study, and interviews. Research has revealed that the application of the school's cultural breeding method at muhammadiyah 2 singaraja high school (3s), b. Clean and healthy living culture (3s), b. breeding of clean and healthy lives, c. breeding of honest do 'a and asmaul husna, d. honest behavior, e. breeding an attitude of responsibility, f. breeding an attitude of discipline, h. understanding the qur 'an.